The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/mra.01260-20
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Amplicon Sequencing of Gut Microbiota in Three Species of Deep-Sea Fish in Suruga Bay, Japan

Abstract: We report here 16S rRNA gene amplicon sequence analysis of the gut microbiota in three species of deep-sea fish collected from Suruga Bay, Japan. Of the three species, two were dominated by the phylum Proteobacteria (genus Photobacterium), while one was dominated by the phyla Spirochaetes (genus Brevinema) and Tenericutes (unclassified Mycoplasmataceae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The dominance of Aeromonas in the gut microbiota suggested that Gymnocypris przewalskii fish were plagued by such pathogens. The findings for other genera and species were similar to the findings of previous studies on the gut microbiota of fishes ( 9 ).…”
Section: Announcementsupporting
confidence: 90%
“…The dominance of Aeromonas in the gut microbiota suggested that Gymnocypris przewalskii fish were plagued by such pathogens. The findings for other genera and species were similar to the findings of previous studies on the gut microbiota of fishes ( 9 ).…”
Section: Announcementsupporting
confidence: 90%
“…2018; Iwatsuki et al . 2021). Lastly, our data showed a different set of microbiota communities than another study using the wild Japanese eel that was captured in three of Taiwan’s rivers.…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota, which facilitate host homeostasis ( 1 , 2 ), have been analyzed in many fish species ( 3 , 4 ) but rarely in deep-sea fish species ( 5 , 6 ). Individuals of Chimaera phantasma (silver chimera) ( 7 ) were caught in a trawl net (depth of approximately 200 to 250 m) off Koshimoda in Suruga Bay, Japan (34.86486N, 138.72713E).…”
Section: Announcementmentioning
confidence: 99%